Exploring the Role of Virtual Collaboration Tools, Remote Working Policies, and Leadership Style in Improving Digital Talent Retention in Indonesia - Syamsulbahri, Syamsulbahri; Young, Felina Co (Eastasouth Institute, 2025)
Digital talent retention is an important issue for any organization because competition in Indonesia keeps pace with rapid changes brought by digitization. The current paper has researched how virtual collaboration tools, remote work policies, and types of leadership have affected digital talent retention. The total selected participants are 120 working in different industries, and they were requested to complete a structured questionnaire quantitatively through a 1-5 Likert scale. Data analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings have indicated that virtual collaboration tools and remote working policy are positively influential toward digital talent retention, and the style of leadership has a great influence on it, acting as a mediator in these relationships. The study develops an integrative framework on the role of technology and flexible policies along with transformational leadership that advocates for a helpful and engaging environment at work. These insights provide a foundation for organizations seeking to attract and retain digital talent in Indonesia's competitive labor market.